Patterns of Pneumonia Disease Distribution Among Toddlers in South Sumatra, Indonesia: A Descriptive Analysis from 2021 to 2023 - Sulfiliana; Sitti nur Aminah; Rianti natasya rusdi; Santi; Shabrina Dwi Artikasari (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Pneumonia is an infectious disease of serious concern because it can affect all age groups, especially toddlers who have a vulnerable immune system. Toddlers are highly susceptible to pneumonia and require special attention in prevention and control efforts. Objectives: This study aims to describe the distribution of pneumonia among under-fives in South Sumatra Province during the 2021-2023 period based on secondary data from the South Sumatra Province Health Profile. Methods: The method used in this study was descriptive quantitative by analyzing secondary data obtained from the South Sumatra Province Health Profile Data were analyzed by organizing the number of pneumonia cases among under-fives per year into tables and graphs, and analyzed narratively to identify patterns and trends in incidence. Results: The analysis showed fluctuations in the number of pneumonia cases among under-fives during the period 2021 to 2023, with some years experiencing a decrease in the number of cases Pneumonia is caused by various pathogens such as bacteria, viruses, and fungi, which are the main factors in the variation of case trends. Conclusion: The distribution of pneumonia among under-fives in South Sumatra Province indicates the need for effective implementation of the Acute Respiratory Tract Infection (ARI) eradication program. This program is an integral part of health development that aims to improve the quality of human resources through the prevention and control of infectious diseases.